Desenvolvimento de uma matriz para liberação controlada do óleo essencial de aroeira (Schinus terebinthifolius Raddi) - Melo, Regina da Silva Acácio (2019)
Essential oils are cited in the literature as promising tools for pest control. Its low stability, which allows rapid degradation by oxidation, temperature and light, makes it necessary to use mechanisms that allow the protection of the oil and the controlled release of it. An alternative is the microencapsulation technique by spray drying, which consists of incorporating the bioactive material into a machine that may be able to impart the encapsulation as the protection and release characteristic to be applied in Integrated Pest Management (IPM). The present work aims to develop a matrix that allows a controlled release of the essencial oil the fruit os Schinus terebinthifolius ant test against the insect-pest os stored graisn L. serricorne. The essencial oil was obtained by hidrodestillation, ans microcapsules with the oil as the core were obtained by spray drying. The characterization of the essential oils was performed by Gas Chromatography coupled to Mass Spectrometry (GC/MS) and Flame Ionization (GC/FID), where 14 compounds were identified. The major compounds were α-pinene (33,49 %), β-pinene (49,8%), 3-carene (5,85%), bornylene (1,21%) and germacrene-D (2,08%). The morfology of the microcapsules was analyzed by Scanning Electron Microscopy (SEM). The thermal stability was evaluated by the thermogravimetry technique in which the microparticles presented stability up to 200 ° C. The bioassays to test the oil activity (1.25 μL, 2.5 μL and 5 μL) and oil-containing and oil-free microparticles versus L. serricorne were performed on a 4-arm olfactometer and were statistically significant in all the tests performed. The pure oil presented repellency in different volumes and the microencapsulation process proved to be efficient in protecting the oil, keeping its repellent capacity.